EXPLORING MATHEMATICS LEARNING PRACTICES AT SMA NEGERI 1 LALOLAE - imelda, imelda; Tahir, Tahir; Chairuddin, Chairuddin; Karunia, Karunia (Universitas Sembilanbelas November Kolaka, 2025)
This study aims to analyze mathematics learning strategies at SMA Negeri 1 Lalolae by exploring teaching methods, learning media, and student responses to identify more effective strategies for improving learning quality. This study employed a qualitative descriptive approach with an exploratory design. Data were collected through classroom observations, interviews with mathematics teachers, and questionnaires completed by 80 students. The findings reveal that lecture and problem-solving methods are most preferred by students, whereas discussion and project-based approaches are still rarely applied. Visual media were found helpful in supporting understanding; however, the use of digital applications remained limited. Students generally responded positively to learning, although their active participation and conceptual understanding still need improvement. The study concludes that the application of varied and appropriate methods and media can foster active student engagement and improve motivation and understanding in learning mathematics.